Deinking paper in a neutral medium, through a treatment with amino acids, in flotation columns - Pineda, J. Gonzalez; García, R. Escudero (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Mixed waste from office paper (MOW) is an excellent source of low-cost, high-quality fiber for the papermaking industry. The limitations in the application of conventional deinking to such paper are related to the negative environmental impacts that chemical substances can cause, which is why deinking in a neutral medium is receiving increasing attention. This study focuses on investigating the effect of the application of the amino acids Aspartate Glutamate and Asparagine, in the deinking of office paper, using a flotation column on a laboratory scale. The methodology involves the sample preparation, a pretreatment, flotation, the manufacture of paper, microscopy analysis, and finally the evaluation of optical properties. Different doses for each of the amino acids and of the mixture of the three were tested, at different conditions of temperature and pH in the pretreatment. The best optical characteristics were obtained when using the mixture of the three amino acids at 0.6% on a dry weight basis of the paper to be deinked, proposed in this study, with 90.8% whiteness. From scanning electron microscopy analysis, no superficial damage to fiber morphology is observed in any of the fiber samples after deinking.